Evaluasi Program Penyaluran Bantuan Pangan Non Tunai (BNPT) Pada Kelompok Masyarakat Miskin di Era Pandemi Covid 19 di Desa Pulung Rejo Kecamatan Rimbo Ilir - Maryam, Siti; Candra, Evita Ayu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The location of the research was carried out in the village of Pulung Rejo, Rimbo Ilir sub-district. This study lasted for 1 month, namely on December 23, 2020 to January 23, 2021. This study aims to find out the regulation of the Minister of Social Affairs Number 20 of 2019, concerning the Distribution of Non-Cash Food Assistance (BPNT) for beneficiary communities in Pulung Rejo Village and to evaluate implementation, constraints and efforts in the Evaluation of the Non-Cash Food Aid (BPNT) Distribution Program for Poor Community Groups in the Era of the Covid-19 Pandemic in Pulung Rejo Village, Rimbo Ilir District in 2020. This study used a qualitative method. The results showed that the implementation of the Non-Cash Food Assistance Distribution Program (BPNT) was not optimal and not well targeted. Obstacles in the implementation of the Non-Cash Food Aid (BPNT) Distribution program to Poor Community Groups in the Covid-19 Pandemic Era in Pulung Rejo Village, Rimbo Ilir District, namely (1) Social service and community participation is still lacking (2) Distribution of basic food assistance or food assistance programs Non-Cash (BPNT) that does not comply with the provisions. (3) Beneficiary families who do not meet the criteria. Efforts were made to overcome these obstacles, namely (1) through a preventive approach and social communication between social services, villages and the community (2) Village government Provide confidence and explanation that non-cash food assistance (BPNT) is assistance provided by the government with the aim of improving nutrition. This means that it is in the form of basic necessities (3) TKSK efforts to verify and validate data means to match existing data with reality by going directly to the field